2021
DOI: 10.2166/wst.2021.455
|View full text |Cite|
|
Sign up to set email alerts
|

Contamination and ecological risk assessment of trace elements in sediments of the Anzali Wetland, Northern Iran

Abstract: In this paper, concentrations of some heavy metals in surficial sediments of the International Anzali Wetland were measured, this wetland is located in northern part of Iran. Sediment pollution levels were examined and analyzed using reliable pollution indices including Pollution Load Index (PLI), Geoaccumulation Index (Igeo) and Enrichment Factor (CF), and finally it was revealed that heavy metal pollution ranged from low to moderated loads in the wetland. According to Sediment Quality Guidelines (SQGs) and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Hasan et al (2016) found very high contamination for Mn, whereas considerable contamination was observed for Pb in the surface water of the Bay of Bengal coast. Esmaeilzadeh et al (2021) found CF for Cr and Mn at 1.0 > CF > 3.0, reflecting moderate pollution in the studied area. Several previous types of the research reported that using fertilizers and fungicides in agricultural lands and rice farms was the primary origin of many heavy metals in the Anzali Wetland (Khosheghbal et al 2013).…”
Section: Pollution Assessmentmentioning
confidence: 73%
See 1 more Smart Citation
“…Hasan et al (2016) found very high contamination for Mn, whereas considerable contamination was observed for Pb in the surface water of the Bay of Bengal coast. Esmaeilzadeh et al (2021) found CF for Cr and Mn at 1.0 > CF > 3.0, reflecting moderate pollution in the studied area. Several previous types of the research reported that using fertilizers and fungicides in agricultural lands and rice farms was the primary origin of many heavy metals in the Anzali Wetland (Khosheghbal et al 2013).…”
Section: Pollution Assessmentmentioning
confidence: 73%
“…Where, 𝐢𝐢 π‘ π‘ π‘ π‘ π‘ π‘ π‘ π‘ π‘ π‘ π‘Ÿπ‘Ÿ and 𝐢𝐢 π‘π‘π‘ π‘ π‘Ÿπ‘Ÿπ‘π‘π‘π‘π‘Ÿπ‘Ÿπ‘π‘π‘π‘π‘Ÿπ‘Ÿπ‘π‘ , respectively, refer to the concentration of a pollutant in the samples (collected directly from the field) and the background (subsurface water) of the study area. CF was widely used to determine the contamination level of heavy metals in the environmental samples (Dat et al 2021;Esmaeilzadeh et al 2021;Hasan et al 2016;Khosheghbal et al 2013). The CF model for heavy metals contamination is given in Table 2 (Dat et al 2021;Hakanson 1980).…”
Section: Contamination Factor (Cf)mentioning
confidence: 99%
“…However, for Mn and Cd, maximum CF values were between 1.0 and 3.0, which denotes moderate contamination Hasan et al (2016). found very high contamination for Mn, whereas considerable contamination was observed for Pb in the surface water of the Bay of Bengal coast Esmaeilzadeh et al (2021). found CF for Cr and Mn at 1.0 > CF > 3.0, re ecting moderate pollution in the studied area.…”
mentioning
confidence: 73%
“…As a coastal wetland, it provides important habitat for birds (the wintering habitat for a variety of waterbird species; [52]) and constitutes a source of fish production in the Caspian Sea. However, in recent decades, Anzali Wetland has been subjected to environmental issues such as urban sprawl and gradual land degradation [53], and biological organisms in the Anzali Wetland are also threatened by toxic substances [54]. Additionally, past research indicated that the agricultural sector could be considered the most important cause of Anzali Wetland degradation [55,56].…”
Section: Discussionmentioning
confidence: 99%